Beaming market simulation to the future by combining agent-based modeling with scenario analysis - Christian Stummer; Lars Lüpke; Markus Günther (Journal of Business Economics, 2021)
Agent-based simulation has become an established method for innovation and technology diffusion research. It extends traditional approaches by modeling diffusion processes from a micro-level perspective, which enables the consideration of various heterogeneous stakeholders and their diverse interactions. While such a simulation is well suited to capture the complex behavior of markets, its application is challenging when it comes to modeling future markets. Therefore, we propose a multi-method approach that combines scenario analysis that generates multiple "pictures of the future" with an agent-based market simulation that offers insight into the potential outcomes of today's strategic (technological) decisions in each of these futures. Thus, simulation results can provide valuable decision support for corporate planners and industrial engineers when they are engaged in technology planning. This paper describes the novel approach and illustrates it through a sample application that is based on an industry-related research project on the development and market introduction of smart products.
Keywords: O33; C53; C63; 650; Agent-based modeling; Scenario analysis; Technology planning; Smart products